The impact of transformation zone representation on the frequency of abnormal cervical cytological results - Zago, Renata Alfena; Camilo-Júnior, Deolino João; Pires D'Ávilla, Solange Correa Garcia; Xavier-Júnior, José Cândido Caldeira [UNESP] (Elsevier, 2023)
Objective: To compare the frequency of abnormal cervical cytological results with and without representation of the transformation zone (TZ) in a medium-sized city in Brazil according to the Bethesda categorization. Methods: We performed an analytical observational study evaluating cytological results over 15 years from conventional smears collected within the Public Brazilian Health System in Araçatuba, Brazil. Tests were stratified by age and cytological result according to Brazilian guidelines and the Bethesda System. Results: There were 261,881 examinations, 159,251 with and 102,630 without TZ representation. The global frequency of abnormal results was higher in smears with TZ representation (crude odds ratio [OR] 4.03; 95% confidence interval [CI] [3.71–4.38]). Considering only women between 25 and 64 years (the target of the national guidelines), there were higher results for high-grade squamous intraepithelial lesions (OR 11.54; 95% CI 6.74–19.78), low-grade squamous intraepithelial lesions (OR 2.82; 95% CI 2.17–3.67) atypical squamous cell in which high-grade intraepithelial lesion cannot be excluded (OR 6.90; 95% CI 4.91–9.66) and atypical squamous cell of undetermined significance (OR 3.53; 95% CI 3.11–4.01) among cases with TZ representation. Conclusion: Samples with TZ representation were associated with higher rates of abnormal results. Health professionals should be regularly trained to understand the weakness of cytological examinations when the TZ is not represented, especially in developing countries.
Keywords: Cytology; Early detection of cancer; Papanicolaou test; Transformation zone; Uterine cervical neoplasms